Who was Julius Caesar? - Medina, Nico; Illustrated by Foley, Tim (New York Penguin Workshop, 2014)
Looks at the life and accomplishments of the ancient Roman general and leader.
Include Illustration and Bibliography
Keywords: Rome (Empire) -- Generals